PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MATEMATIKA BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI PENGENALAN BANGUN DATAR KELAS I SDN 26 CAKRANEGARA TAHUN AJARAN 2025/2026 - Yuliatin, Yumni; Ramli; Ruqoiyyah, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the lack of innovative and engaging mathematics teaching materials, especially on the topic of plane shapes in Grade I at SDN 26 Cakranegara. This study aimed to determine the validity and practicality of the Contextual Teaching and Learning (CTL)-based student Worksheet (LKPD) on plane shapes for Grade I students based on validation questionnaires from media experts, material experts, teachers, and students. This study used the Research and Development (R&D) method with the 4D model consisting of define, design, develop, and disseminate. However, the research was limited to the develop stage. Data collection techniques included interviews, questionnaires, and documentation. The instruments consisted of interview guidelines and questinnaires, including media expert validation sheets, material expert validation sheets, and teacher and student response questionnaires. The data were analyzed using qualitative and quantitative analysis. Qualitative data were obtained from comments and suggestions of validators, while quantitative data were obtained from questionnaire scores. The results showed that the CTL-based LKPD obtained a media expert validation score of 95% and a material expert validation score of 86.67%, both categorized as very valid. In addition, the teacher response score reached 89.33% and the student response score reached 95.40%, both categorized as very practical. Therefore, the CTL-based LKPD was declared feasible and practical to be used as teaching material on plane shapes for Grade I elementary school students.